Overexpression of BIT33_RS14560 Enhances the Biofilm Formation and Virulence of Acinetobacter baumannii - Yang, Ruifu; Lai, Bipeng; Liao, Kang; Liu, Baomo; Huang, Lixia; Li, Shaoli; Gu, Jincui; Lin, Ziying; Chen, Yili; Wang, Shuaishuai; Qiu, Yanli; Deng, Jiating; et al. (Frontiers in Microbiology, 2022)
Acinetobacter baumannii, a strictly aerobic, non-lactose fermented Gram-negative bacteria, is one of the important pathogens of nosocomial infection. Major facilitator superfamily (MFS) transporter membrane proteins are a class of proteins that widely exists in microbial genomes and have been revealed to be related to biofilm formation in a variety of microorganisms. However, as one of the MFS transporter membrane proteins, little is known about the role of BIT33_RS14560 in A. baumannii. To explore the effects of BIT33_RS14560 on biofilm formation of A. baumannii, the biofilm formation abilities of 62 isolates were firstly investigated and compared with their transcript levels of BIT33_RS14560. Then, this specific gene was over-expressed in a standard A. baumannii strain (ATCC 19606) and two isolates of extensively drug-resistant A. baumannii (XDR-Ab). Bacterial virulence was observed using a Galleria mellonella infection model. High-throughput transcriptome sequencing (RNA seq) was performed on ATCC 19606 over-expressed strain and its corresponding empty plasmid control strain. Spearman’s correlation analysis indicated a significant negative correlation (R = −0.569, p = 0.000) between the △CT levels of BIT33_RS1456 and biofilm grading of A. baumannii isolates. The amount of A. baumannii biofilm was relatively high within 12–48 h. Regardless of standard or clinical strains; the biofilm biomass in the BIT33_RS14560 overexpression group was significantly higher than that in the control group ( p < 0.0001). Kaplan–Meier survival curve analysis showed that the mortality of G. mellonella was significantly higher when infected with the BIT33_RS14560 overexpression strain (χ2 = 8.462, p = 0.004). RNA-Seq showed that the mRNA expression levels of three genes annotated as OprD family outer membrane porin, glycosyltransferase family 39 protein, and glycosyltransferase family 2 protein, which were related to bacterial adhesion, biofilm formation, and virulence, were significantly upregulated when BIT33_RS14560 was over-expressed. Our findings provided new insights in identifying potential drug targets for the inhibition of biofilm formation. We also developed a practical method to construct an over-expressed vector that can stably replicate in XDR-Ab isolates.